Karakteristik Keilmuan Ilmu Hukum Empirik - Lalu Husni (Fakultas Hukum Universitas Mataram, 2012)
Jurisprudence may be differenhciated into normative jurisprudence and empirical jurisprudence. Based on the philosophical view, they have theirself characteristic. Ontologically, the study object of empirical jurisprudence is focused on the law as a set of human behavior (law in action). Empirical jurisprudence (Sociological Jurisprudence) gives equal attention to the society and law as two primary elements in legal application. Epistimologically, the truth in empirical jurisprudence is obteined in accordance with the scientific norm (scientific method) in general. From the axiology perspective, the perspective of empirical legal srtudy is absolutely importance in achieving the statutes neccessary to fuolfill the legal neccessity of the society, so as to it more effective in its application.